Settlement Improvement of Weak Soil of Natural Moisture Content by Using Geogrid Reinforcement Under Different Dynamic Load (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
One of new method to improve the bearing capacity of weak soil is  by using  geosynthetic reinforcement materials that has become more common in past 40 years for a number of applications to reduce the cost of maintences by increasing design life. This study concerned with the behavior of weak soil and the amount of settlement that happened when the soil exposed to different weight load with different number of blows . Field and laboratory tests done to calculate soil settlement. For experimental tests a model with dimension (150×75×75cm) has been manufactured, clayey silty sand soil in model exposed to different dynamic weight by using load with ( 4.5kg), load with (7.5kg) and load with (10kg). Each load strick the soil with 9 5 and 10) blows during an experiment for each dynamic load. 12 Laboretory experiments were conductedon 38 test points, 6 experiments done on soil without geogrid and 6 experiments done on soil with geogrid that included 19 test point for each case.The experiments tests show that by increasing the weight load and increasing in number of blows settlement increase in both cases ( without and with geogrid). The experiments show that by using geogrid the settlement decrease comparison with the amount of soil settlement without geogrid. By using geogrid and exposed to weight loads ( 4.5, 7.5 and 10kg.) with No. of blows = 5 the average percent in settlement decrease 1.2, 2.1,1.7%) and with No. of blows =10 for the same loads the average percent of settlement decrease (1.8, 2.7, 2.7%).